Successful Radiofrequency Catheter Ablation of The Para-Hisian Accessory Pathway in A Patient with Wolf Parkinson White Syndrome - Ismir Fahri; Yoga Yuniadi; Dicky A Hanafy; Hauda El Rasyid (The Indonesian Heart Association, 2011)
Radiofrequency catheter ablation of the accessory pathway in Wolff-Parkinson-White (WPW) syndrome is a highly successful mode of therapy. Sudden cardiac arrest survivors associated with WPW syndrome should undergo radiofrequency catheter ablation. Para-Hisian is one of unusual location accessory pathway in WPW syndrome associated with high risk complication of complete AV block during catheter ablation. Here we describe a case of patient who presented with history of palpitation due to WPW syndrome, electrophysiology study identified a para-Hisian accessory pathway so close to His bundle that discrete site between the pathway, the first ablation was unsuccessful and terminated due to the risk of complete AV block. The accessory pathway was successfully ablated in a second session using radiofrequency, although this entailed a great increase in the risk of causing complete atrioventricular block.